Implementation of Picture and Picture Model to Improve Learning Outcomes of Islamic Religious Education Classes in Elementary Madrasahs - Solehati, Solehati; Takwim, Mardi; Al-Hamdany, Zuljalal (South Sulawesi Education Development (SSED), 2025)
Through the Picture and Picture learning model, this research aims to improve the learning outcomes and activities of grade III MI students in Islamic Religious Education subjects. The method used is classroom action research in two cycles, each consisting of planning, implementation, observation, and reflection. The results show that this model effectively improves student learning outcomes, with learning completeness initially only 16% in the first Cycle, increasing to 100% in the second. Student activity also increased from 47% (